2006
DOI: 10.1097/01.jnen.0000218444.53405.f0
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Is a Negative Modulator of Adult Neurogenesis

Abstract: Transforming growth factor (TGF)-beta1 has multiple functions in the adult central nervous system (CNS). It modulates inflammatory responses in the CNS and controls proliferation of microglia and astrocytes. In the diseased brain, TGF-beta1 expression is upregulated and, depending on the cellular context, its activity can be beneficial or detrimental regarding regeneration. We focus on the role of TGF-beta1 in adult neural stem cell biology and neurogenesis. In adult neural stem and progenitor cell cultures an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
157
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 72 publications
10
157
2
Order By: Relevance
“…Although a variety of growth and trophic factors are upregulated following ischemic injury, some are stimulators of neural progenitor proliferation, whereas others block the self-renewal of cells. For example, TGF␤1 can directly block cell division 42 by upregulating the expression of cell cycle inhibitors, whereas migration of cells away from their mitogenic niche can also promote cell cycle exit and inhibit cell division. 8 It is important to note that ischemia-induced migration of neuroblasts has been shown to be due to the expression of MCP-1, 44 which can attract the progenitor cells away from the neurogenic niche, blocking their proliferation.…”
Section: Role Of Neural Stem Cellsmentioning
confidence: 99%
“…Although a variety of growth and trophic factors are upregulated following ischemic injury, some are stimulators of neural progenitor proliferation, whereas others block the self-renewal of cells. For example, TGF␤1 can directly block cell division 42 by upregulating the expression of cell cycle inhibitors, whereas migration of cells away from their mitogenic niche can also promote cell cycle exit and inhibit cell division. 8 It is important to note that ischemia-induced migration of neuroblasts has been shown to be due to the expression of MCP-1, 44 which can attract the progenitor cells away from the neurogenic niche, blocking their proliferation.…”
Section: Role Of Neural Stem Cellsmentioning
confidence: 99%
“…Acute up-regulation of TGFβ1 after brain injury may be beneficial due to its positive effect on neurogenesis 50,51 . However, when TGFβ1 expression levels remain chronically elevated, it may affect the cell cycle of neural progenitor cells and inhibit neurogenesis by prolonging G1 and/or increasing cell cycle exit 49,52 . A similar effect on neurogenesis occurs during normal mammalian CNS development, when TGFβ has been reported to inhibit neural stem cell proliferation.…”
Section: Molecular Pathways and Tumorigenesismentioning
confidence: 99%
“…In this regard, we and others reported that intracerebroventricular infusions of TGF-b into the rat brain or overexpression of TGF-b in transgenic mice resulted in a marked downregulation of cell proliferation and neurogenesis in the hippocampus. 57,58 Moreover, levels of TGF-b are known to be increasing in the brain along with ageing. 59,60 Additional experiments targeting specifically the individual signaling systems are required to elucidate in the age-dependent loss of fluoxetine activities on neurogenesis.…”
mentioning
confidence: 99%